Predictors of Spelling and Reading Performance in Logopenic Variant Primary Progressive Aphasia. - Nickels, Katlyn V.; Kielar, Aneta (Journal of Speech, Language & Hearing Research, 2025)
Purpose: The purpose of this study was to comprehensively examine written language performance in logopenic variant primary progressive aphasia (lvPPA) by (a) characterizing the types of errors made during single-word spelling-to-dictation and oral reading; (b) examining the role of phonological, semantic, and phonology--orthography transcoding skills on spelling and reading performance; and (c) exploring the influence of psycholinguistic properties on spelling and reading accuracy. Method: Twenty-two individuals with lvPPA and 21 neurotypical controls performed comprehensive language assessment that included spelling to dictation and oral reading of pseudowords and real words with regular or irregular sound--letter correspondences. Factor scores representing phonological, semantic, and phonology--orthography transcoding skills were entered into multiple linear regressions to determine the degree to which these skills predicted performance on spelling and reading tasks. The psycholinguistic properties of real word stimuli were extracted at the item level and entered as predictors of spelling and reading accuracy in stepwise linear regression analyses. The mediating role of psycholinguistic properties on the relationship between semantics and phonology and spelling of real words was also explored. Results: Pseudoword spelling performance was predicted by phonology--orthography transcoding skills. Spelling accuracy for regular words was predicted by semantics, phonology, and transcoding, whereas irregular word spelling performance was predicted by semantics and transcoding. Semantic neighborhood density, frequency, and imageability were significant predictors of spelling accuracy, while age of acquisition and imageability predicted reading accuracy. Semantic neighborhood density mediated the relationship between phonology and regular word spelling accuracy, whereas frequency mediated the relationship between semantics and irregular word spelling accuracy. Conclusions: The results of this study contribute to the understanding of language processes underlying spelling and reading performance in lvPPA. Specifically, we provide insights regarding the differential influence of phonological and semantic abilities on written language in lvPPA, and we highlight the importance of the psycholinguistic properties of linguistic stimuli in spelling and reading performance. Supplemental Material: https://doi.org/10.23641/asha.30594788